Three new species of Pheidole Westwood, 1839 (Hymenoptera: Formicidae: Myrmicinae: Attini) from central Mexico - Vázquez-Franco, César Maximiliano; Castaño-Meneses, Gabriela; Casanova, Leticia Ríos-; Morrone, Juan J. (Zootaxa, 2024)
Pheidole is the richest ant genus in the world. We describe herein three new species from the state of Puebla, Mexico: P. jolalpanensis sp. nov., P. latiscava sp. nov. and P. rojasae sp. nov. Additionally state records and notes are provided for P. lamia Wheeler 1901 and P. polymorpha Wilson 2003 for the Mexican states of Veracruz and Querétaro, respectively. Parts of Wilson’s taxonomic keys are modified to allow the identification of the new species.